Ecoliteracy Analysis and Science Teaching Materials: Survey in Junior High Schools - Ghina Nisrina Ramadhanti; Indarini Dwi Pursitasari; Indriyani Rachman (Pascasarjana Universitas Negeri Malang (UM), 2023)
The study aims to analyze ecoliteracy and the teaching materials required for 21st century learning these days. The study employs the survey method by involving population of 104 junior high school students in grade VIII in Bogor City. The data are collected using ecoliteracy tests and interviews and analyzed using descriptive statistics techniques. The results showed that 48 students (46.15 percent) fall into the category of lacking ecoliteracy cognitive competence. The results of the questionnaire on the competence of attitudes, skills, and human relations with nature fall into the medium category. Therefore, in order to support the improvement of students’ ecoliteracy, interactive teaching materials are required in order to attain more meaningful environmental learning.DOI: 10.17977/jps.v11i12023p020